The Effect of the Guided Inquiry Model on the Reasoning Abilities of Elementary School Students - Maulidiyah, Nur; Wulandari, Fitria (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to determine the effect of the guided inquiry learning model on students' reasoning ability in science subjects in class V SD Muhammadiyah 5 Porong. Using a quantitative approach, this type of research is a pre-experimental one-group pretest-posttest. The population in this study were all fifth-grade students of SD Muhammadiyah 5 Porong, with a total of 22 students. The sample in this study is to use saturated samples because the number of students is less than 30, with a total of 22 students. Primary data is in students' pretest and posttest reasoning ability test results and secondary data is in photo documentation. Data collection is done by giving reasoning ability tests to students. The collected data were analyzed using hypothesis testing using the paired t-test formula. The results of hypothesis testing using paired t-tests stated that the results of the significance value of 0.066, which means > 0.05, so that Ha is accepted, and H0 is rejected. There is an effect of using the guided inquiry learning model on the reasoning ability of elementary school students in learning science.